Jovens e Políticas Públicas: Representações sociais de educação entre jovens do ProJovem Urbano na cidade de João Pessoa /PB - Silva, ângela Cardoso Ferreira (2011)
This study had as a goal to know the social representation from the education among young from ProJovem Urban,in the city of João Pessoa / PB. The study of education as a social represented goal by young people is necessary because it provides greater understanding of their socio-cognitive elaborations. The research was structured around a core of young ProJovem Urban from João Pessoa / PB, involving 132 people. The theoretical and methodological established itself around the theory of social representations, developed by Serge Moscovici, and in this context, the central core theory, formulated by Jean-Claude Abric, which recommends the structural approach from the social representations. In addition to literature review and analysis of the documents relating to the Program, we had three analytical moments. Initially we seek knowledge about the group it represents, based on data of social and economic aspects of young people through questionnaires. The second period brought the understanding of the content and organization of social representation, from the application of the technique of free association of words TAPL( Portuguese). The analysis of the semantic units obtained through the combined frequency TALP (Portuguese) medium order of evocations. Finally we depth interviewed, as obtained with the practical dimensions of social representation in question. To analyze the corpus of discourse that emerged in this research, we follow the guidelines of content analysis according to Bardin (1977) and Franco (2007). The elements of learning, knowledge and be someone likely to constitute the core of social representations of education. These significant up what is most fundamental and rooted in the conception of young people to education. It is believing they can overcome situations of exclusion and improving the life that young people choose to go back to school. Our analysis of the social representation of Education achieves bring clarifications about the relationship between young people with education, from cognitive, symbolic and ideological discourse that hatch from the subjects.